More than just a broken limb: Unmasking CRPS in Pakistan - Zahra Aamir Khan (Journal of the Pakistan Medical Association, 2025)
Madam, Complex Regional Pain Syndrome (CRPS) is a debilitating pain disorder, usually affecting one limb, and occurring after a trauma. It is marked by intense pain out of proportion to the severity of the initial injury. Because CRPS is a rare condition, its pathophysiology, diagnosis, and treatment are not completely understood. The pathophysiology might involve an interplay between inflammation, genetics, nervous system changes, and psychological influences1. Despite the challenges in diagnosis, the currently accepted diagnostic criteria is the Budapest Criteria, established after revising the previous IASP Criteria which led to overdiagnosis.2 Once CRPS is identified, therapy can be just as complicated. The UK Royal College of Physicians outlines a multidisciplinary approach based on each patient’s individual needs.3 This involves patient education, utilizing intervention and medications for the pain, physical rehabilitation, and psychological intervention. Each of these elements is equally important for recovery. Older studies indicate a significant delay in CRPS diagnosis, with patients waiting an average of 4 years.4 The lack of knowledge among physicians, unnecessary surgeries, and the belief that patients might be exaggerating about their pain, all contribute to a delayed diagnosis. This leads to a further decline in limb function, muscle wasting, difficulty in performing everyday activities, and eventually, social isolation. To improve the understanding of CRPS in low-resource settings with limited patient data, Lewis et al. presented a global series from 9 different countries, including Pakistan.5 Despite being the world’s 5th most populous country, Pakistan lacks sufficient CRPS prevalence and presentation data. Out of the identified patients, only 16% were diagnosed according to the globally recognized Budapest criteria, and for 65% of patients, only pharmacological intervention was used. The essential multidisciplinary approach was rarely used. This highlights several issues that need to be resolved. This letter calls for localized research to help refine management protocols tailored to the Pakistani population. By raising awareness about the clinical features of CRPS and the consequences of neglect towards patients, we can promote timely diagnoses and avoid long-term complications. Physicians need to build trust with their patients and make them feel heard. CRPS is a complicated condition, so a culture of strict adherence to standardized diagnostic and management approaches must be created. Integration of said protocols into the healthcare curriculum is also essential. This comprehensive approach requires immediate implementation to improve quality of life and reduce unnecessary suffering.